1997
DOI: 10.2169/internalmedicine.36.62
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Cryoglobulinemia Associated with Cutaneous Vasculitis and Pulmonary Symptoms.

Abstract: A 45-year-old Japanese man with Sjogren's syndrome developed recurrent skin ulcers, palpable purpura, and dyspnea. Serum mixed-type cryoglobulin level was elevated. A biopsy of his skin lesion showedthe characteristic leukocytoclastic vasculitis of mixed-type cryoglobulinemia. Dyspnea, skin ulcers, and purpura resolved along with a reduction in the serum cryoglobulin level after prednisolone administration. This patient demonstrated cryoglobulinemia-associated vasculitis, as well as possible cryoglobulinemia-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other authors have reported vasculitis in 30% of both primary and secondary SS patients [13]. Palpable purpura is also found in SS patients [14] with biopsies showing leukocytoclastic vasculitis [12] and may be associated with central nervous system involvement [15] or pulmonary involvement [16].…”
Section: Manifestations and Differential Diagnosis In The Pediatric P...mentioning
confidence: 99%
“…Other authors have reported vasculitis in 30% of both primary and secondary SS patients [13]. Palpable purpura is also found in SS patients [14] with biopsies showing leukocytoclastic vasculitis [12] and may be associated with central nervous system involvement [15] or pulmonary involvement [16].…”
Section: Manifestations and Differential Diagnosis In The Pediatric P...mentioning
confidence: 99%
“…(Bernacchi et al, 2004). Palpable purpura is also found in SS patients (Alexander and Provost, 1987) with biopsies showing leukocytoclastic vasculitis (Ramos-Casals et al, 1998) and may be associated with central nervous system involvement or pulmonary involvement (Konishi et al, 1997).…”
Section: Cryoglobulinemia Is Divided Into Three Clinical Subsets: Typmentioning
confidence: 99%
“…Cryoglobulinemia is associated with various overlying diseases and involves a variety of symptoms such as purpura, arthralgias, neuropathies, and hepathic and renal involvement. 2,3 Severe vasculitic complication, such as digital necrosis, is very rare and predominantly affects small vessels. Arteritis of small-and medium-sized vessels is present in a significant number of patients with systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 99%